A Comprehensive Systematic Review of Relationship Between Hba1c Levels and The Risk of Diabetic Retinopathy - Ayusti Mutazila; Muhamad Ridho (The International Journal of Medical Science and Health Research, 2026)
Introduction: Diabetic retinopathy (DR) remains a leading cause of preventable blindness worldwide, with glycemic control identified as a critical modifiable risk factor. Despite extensive research, evidence gaps persist regarding optimal HbA1c thresholds, the role of glycemic variability, and the consistency of the HbA1c-DR relationship across diverse populations. This systematic review aims to comprehensively synthesize global evidence on the association between HbA1c levels and DR risk, severity, and progression. Methods: A systematic review was conducted following PRISMA guidelines. We screened studies based on predefined criteria including diabetes population, HbA1c measurement, DR outcome assessment, and study design. Data extraction encompassed study characteristics, HbA1c measurement methodology, DR assessment methods, association measures, moderating factors, and statistical approaches. The review synthesized evidence from 200 included studies encompassing diverse geographic regions and both Type 1 and Type 2 diabetes populations. Results: A strong, consistent positive association between elevated HbA1c and DR risk was demonstrated across all study designs and populations. Quantitative synthesis revealed that a 10% relative reduction in HbA1c decreases retinopathy progression risk by 43-45%, and each 1% absolute HbA1c reduction confers approximately 35% risk reduction. Mean HbA1c levels were consistently higher in DR patients versus those without (range: 8.09-9.50% vs. 7.21-8.49%). A dose-response relationship was evident, with progressive HbA1c elevation correlating with increasing DR severity. Threshold effects were identified at 7.0%, with substantially accelerated risk above 8.6%. HbA1c variability emerged as an independent predictor. Diabetes duration, hypertension, and dyslipidemia significantly moderated the relationship. Conclusion: This review establishes HbA1c as a dominant, modifiable, dose-dependent risk factor for diabetic retinopathy across all diabetes types and populations. No absolute safe threshold exists; risk reduction follows HbA1c improvement continuously. We recommend intensive, early glycemic control targeting individualized HbA1c goals, integrated multifactorial risk management, and incorporation of HbA1c variability into risk stratification. Future research should focus on establishing population-specific thresholds and investigating HbA1c variability intervention strategies.